Réponses

Meilleure réponse !
2013-09-03T18:28:37+02:00
   Avec :   a  =  -2   et   b  =  6     on a :

   (-a)b  =  -(-2) × 6
             =  2 × 6
             =  12

   -(ab)  =  -(-2 × 6)
             =  -(-12)
             =  12

   a(-b)  =  -2 × -(6)
             =  -2 × -6
             =  12

 
  (-a)(-b)  =  -(-2) × -(6)
                =  2 × -6
                =  -12
  • Cetb
  • Modérateur confirmé
2013-09-03T18:29:14+02:00
(-a)b :  (-(-2))6=2*6=12     
- (ab) : -((-2)6) = -(-12)=12
a(-b)  : -2(-6) = 12         
(-a)(-b) : = -(-2)(-6)=-12